The prognostic role of sex and hemoglobin levels in patients with oral tongue squamous cell carcinoma - Tagliabue, Marta; D’Ecclesiis, Oriana; De Berardinis, Rita; Gaeta, Aurora; Martinoli, Chiara; Piana, Andrea Fausto; Maffini, Fausto; Gandini, Sara; Ansarin, Mohssen; Chiocca, Susanna (Frontiers in Oncology, 2022)
Background: Women and men differ genetically, biologically (sex) and by social construct (gender), possibly impacting on prognostic factors in predicting cancer survival. Hemoglobin levels and immune system activation are players acting in this scenario which could play a role in partly determining prognosis between patients of different sex/gender (S/G). Here, we investigate these factors in patients affected by tongue squamous cell carcinoma. Methods: This is an observational retrospective cohort study. We collected tongue cancer patients’ clinical data, including hemoglobin levels and neutrophil lymphocyte ratio (NLR). Overall survival (OS) and disease-free survival (DFS) were compared between women and men considering confounding and prognostic factors in multivariate Cox proportional hazard models. Stratified analyses were also conducted by sex and tumor stage. Result: 576 patients, 39.9% women and 60.1% men, were found eligible for the analysis. Men were more often smokers (p<0.001), alcohol consumers (p<0.001), overweight or obese (p<0.001) and undergoing radiotherapy (RT) (p=0.002). By multivariate models for stage I-II, men showed half risk of death and relapse than women (HR=0.44; 95% CI 0.24-0.81, p=0.009; HR=0.55; 95% CI 0.34-0.87, p=0.01, for OS and DFS respectively). Moreover, low hemoglobin levels appeared to be an independent prognostic factor for women but not for men in terms of both OS and DFS. Specifically, women with low hemoglobin levels showed a worse OS and DFS (HR=2.15; 95% CI 1.23-3.78; HR=1.77; 95% CI 0.95-2.97, respectively). Low hemoglobin levels appeared to be a poor OS prognostic factor for women at stage I-II (p<0.004) but not for men (p=0.10). For women in advanced stage, NLR>2.37 was associated with a significant increase in relapse (p<0.03). Conclusion: In our cohort of patients with oral tongue squamous cell carcinoma, men present better OS and DFS than women in early stages. Low hemoglobin levels appear to be an independent prognostic factor for women, especially when early-stage tumors are considered. For advanced stages (III-IV), sex is not a significant factor related to patients’ prognosis.